Holistic assessment of the microbiome dynamics in the substrates used for commercial champignon (Agaricus bisporus) cultivation. Issue 6 (27th July 2020) - Carrasco, Jaime; García‐Delgado, Carlos; Lavega, Rebeca; Tello, María L.; De Toro, María; Barba‐Vicente, Víctor; Rodríguez‐Cruz, María S.; Sánchez‐Martín, María J.; Pérez, Margarita; Preston, Gail M.
Summary: Microorganisms strongly influence and are required to generate the selective substrate that provides nutrients and support for fungal growth, and ultimately to induce mushroom fructification under controlled environmental conditions. In this work, the fungal and bacterial microbiota living in the different substrates employed in a commercial crop (compost phase I, II and III, flush 1 and 2, and casing material on day 1, 6 and 8 after compost casing and during flush 1 and 2) have been characterized along the different stages of cultivation by metataxonomic analysis (16S rRNA and ITS2), analysis of phospholipid fatty acid content (PLFAs) and RT‐qPCR. Additionally, laccase activity and the content of lignin and complex carbohydrates in compost and casing have been quantified. The bacterial diversity in compost and casing increased throughout the crop cycle boosted by the connection of both substrates. As reflected by the PLFAs, the total living bacterial biomass appears to be negatively correlated with the mycelium of the crop. Agaricus bisporus was the dominant fungal species in colonized substrates, displacing the pre‐eminent Ascomycota, accompanied by a sustained increase in laccase activity, which is considered to be a major product of protein synthesis during the mycelial growth of champignon. From phase II onwards, the metabolic machinery of the fungal crop degrades lignin and carbohydrates in compost, while these components are hardly degraded in casing, which reflects the minor role of the casing for nourishing the crop. The techniques employed in this study provide a holistic and detailed characterization of the changing microbial composition in commercial champignon substrates. The knowledge generated will contribute to improve compost formulations (selection of base materials) and accelerate compost production, for instance, through biotechnological interventions in the form of tailored biostimulants and to design environmentally sustainable bio‐based casing materials. Abstract : The techniques employed in this study provide a holistic and detailed characterization of the changing microbial composition in commercial champignon substrates. The knowledge generated will contribute to improve formulations through biotechnological interventions.